Sustainable Innovation Strategies In Business and Management: Analysis Of Key Factors and Impact - Yulitasari, Lis; Suryanto, Tulus; Hilal, Syamsul (Publication Division of International Ecsis Association, 2023)
Innovation has become a key element in business sustainability, and companies that can integrate sustainable innovation into their strategy have a better chance of surviving and growing in a rapidly changing environment. This research will explore key factors influencing the development and implementation of sustainable innovation strategies in various types of organizations, including internal factors such as innovation culture, leadership, and resources, as well as external factors such as regulatory pressures and consumer demands for sustainable products and services. This research method involves a qualitative with multiple-case study. This study highlights five critical success factors for implementing sustainable innovation strategies in companies: leadership commitment, dedicated divisions, substantial investments in internal capabilities, long-term collaboration with external stakeholders, and culture-fostering experimentation. The impacts include increased revenue from sustainable products, improved production efficiency, energy savings, emissions reduction, and enhanced local supplier chains, reinforcing the case for broader adoption. The implications of these findings include the importance of empirical data in convincing companies to adopt sustainable innovation strategies. Further research is recommended, especially in companies with a more advanced and radical level of maturity in implementing sustainability innovation strategies.